SISTEM PENGENDALIAN KETINGGIAN AIR DENGAN METODE PID BERBASIS PLC SIEMENS S7-1200 - Silawardono; Hatib Setiana; Zagas Ferdyan (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
This research aims to design and implement a Siemens S7-1200 Programmable Logic Controller (PLC) based water level control system using the PID (Proportional Integral Derivative) control method with autotuning. The system is designed to automatically adjust the water level in the tank with high precision, using an ultrasonic sensor for height measurement and a water pump controlled by an inverter for water level adjustment. Test results show that the system is able to maintain stability and accuracy in achieving the specified setpoint, with a low error rate. An error of 4% was recorded at most setpoints, while at certain setpoints, such as 16 cm, no error was found. This shows that the designed control system has successfully met the main objective of controlling the water level efficiently and reliably.